The efficacy and safety of riluzole for neurodegenerative movement disorders: a systematic review with meta-analysis - Jia Liu; Lu-Ning Wang (Taylor & Francis Group, 2018)
Neurodegenerative movement disorders mainly include Parkinson's disease, atypical parkinsonisms, Huntington disease, and hereditary ataxia. Riluzole is the only drug approved by the US Food and Drug Administration for amyotrophic lateral sclerosis. The neuroprotective effects of riluzole have been observed in experimental models of neurodegenerative movement disorders. In this paper, we aimed to systematically analyze the efficacy and safety of riluzole for patients with neurodegenerative movement disorder. We searched the electronic databases such as PubMed, EMBASE, CINAHL, Cochrane Library and China National Knowledge Infrastructure until June 2017 for the eligible randomized controlled trials, as well as the unpublished and ongoing trials. For continuous data, we calculated standardized mean differences with 95% confidence intervals if studies did not use the same scales to measure outcomes. For dichotomous data, we calculated risk differences if a trial reported no adverse events or dropouts. We pooled the results using a random-effects model. We included nine studies with 1320 patients with neurodegenerative movement disorders, which compared riluzole with placebo. No significant difference was found in the number of participants with adverse events but with motor improvement in hereditary ataxia. There were only two studies focusing on neuroprotective effect. Riluzole is well-tolerated in the patients with neurodegenerative movement disorders. Riluzole seems to be promising for patients with hereditary ataxia in symptomatic effect, which needs to be further confirmed by well-designed studies in the future. Moreover, it makes sense to design long-term study focusing on neuroprotective effect of riluzole in disease-modifying.